Acoustic observation of ice rifting and breaking events on the Antarctic ice shelf using remote hydroacoustic listening stations - Li, Binghui (Curtin University, 2010)
Long-term continuous monitoring of ice break-up on ice shelves and icebergs in Antarctica is essential for a global observation system of climate change and its consequences. While calving of massive pieces of ice from the Antarctic ice shelf is well observed from satellites, numerous ice breaks of smaller volume cannot be systematically monitored and statistically analysed by the existing means of remote sensing and local in-situ observations. This study aimed to investigate the feasibility of an alternative monitoring approach based on remote acoustic observations of ice rifting and breaking events on Antarctic ice shelves and icebergs using distant underwater acoustic listening stations in the ocean. This investigation was carried out using long-term continuous sea noise recordings made from 2002 to 2007 at two hydroacoustic stations deployed in the Indian Ocean as part of the International Monitoring System of the Comprehensive Nuclear-Test-Ban Treaty: off Cape Leeuwin in Western Australia (HA01) and off Chagos Archipelago (HA08).Investigations of a number of scientific and technical issues relevant to the main objective were carried out in this study. They include: 1) processing of the CTBT hydroacoustic data from the two IMS stations with the aim of detecting and identifying signals received from Antarctic ice breaking events; 2) investigating the time-frequency arrival structure of the signals expected from ice events using experimental data and numerical modelling of acoustic propagation from Antarctica to the IMS stations in the Indian Ocean; 3) analysing the bearing accuracy of the IMS stations; 4) examining three different schemes for localization of ice events using either one or two IMS stations; 5) analysing the spatial distribution of Antarctic ice events observed over 6 years of data collection and its correlation with the major glacial features of the Eastern Antarctic coastal zone which are most likely sources of newly calved icebergs and underwater noise produced by ice breakup; 6) analysing long-term variations in the occurrence of ice events and their links with changes in climate related metocean characteristics of the Eastern Antarctic coastal zone.A number of important findings and conclusions were made based on the results of this study. It was revealed that Antarctica is one of the major sources of low-frequency underwater noise at the two IMS stations in the Indian Ocean. The transient signals received at the IMS stations from Antarctic ice events consist mainly of a mode one arrival pulse with strong frequency dispersion, which is due to the acoustic propagation characteristics in the near-surface acoustic channel of the polar ocean environment south of the Antarctic Convergence Zone (ACZ). Both HA01 and H08S stations have bearing estimate accuracy for transient acoustic noise in Antarctica of about 0.2° RMS. The bearing error of HA01 also has a systematic component of around 0.8° clockwise. The bearing deviation induced by horizontal refraction of acoustic propagation across the ACZ polar frontal zone and over the continental slopes can be considerable, up to 1° for sources located in the easternmost and westernmost parts of the Eastern Antarctic coastal zone observed from the IMS stations. The localization of Antarctic ice events can be achieved either by triangulation using bearing estimates, if the same event can be detected at both stations, or by estimating the range to the noise source through inversion of mode 1 dispersion characteristic when the signal is detected only at one station.The location of ice events in the Antarctic coastal zone can also be coarsely estimated from the low cut-off frequency of mode 1 measured at the receive station. The majority of ice events observed at HA01 were located within a number of back-azimuth sectors which correspond to the directions to the ice shelves and iceberg tongues which are known as active zones of ice break-up in Eastern Antarctica. The temporal changes in the occurrence frequency of ice events detected at HA01 reveal strong seasonal variations but no significant interannual trend.Based on the main results and findings, this study achieved its primary aim to demonstrate the feasibility of remote monitoring of ice rifting and breaking events on Antarctic ice shelves and icebergs using the IMS hydroacoustic listening stations deployed in the Indian Ocean.